2018
DOI: 10.1002/jmv.25207
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor chidamide promotes reactivation of latent human immunodeficiency virus by introducing histone acetylation

Abstract: Highly active antiretroviral therapy can reduce the human immunodeficiency virus (HIV) viral load in the plasma to undetectable levels. However, because of the presence of latent HIV reservoirs, it is difficult to completely eradicate HIV in infected patients. Our objective was to assess the potency of chidamide, a novel histone deacetylase inhibitor recently approved for cancer treatment by the China Food and Drug Administration, to reactivate latent HIV-1 via histone acetylation. Viral reactivities of chidam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Latency reversing activity of MS‐275 was examined in combination with other molecules including buthionine sulfoximine, a glutathione‐synthesis inhibitor; prostratin, a nontumor‐promoting phorbol ester; and 5‐aza‐2′deoxycytidine, a DNA demethylating agent, and these studies reported various levels of potency, which is likely the result of differences in HIV‐1 reporter virus at different chromosomal regions. The related compound chidamide (Figure ), showed better cell tolerance than the commonly used broad‐spectrum HDAC inhibitor suberoylanilide hydroxamic acid (SAHA), and was also able to disrupt viral silencing in primary CD4 + T cells isolated from patients …”
Section: Lras Identified From Small Molecule Screens Exhibit Diverse mentioning
confidence: 99%
“…Latency reversing activity of MS‐275 was examined in combination with other molecules including buthionine sulfoximine, a glutathione‐synthesis inhibitor; prostratin, a nontumor‐promoting phorbol ester; and 5‐aza‐2′deoxycytidine, a DNA demethylating agent, and these studies reported various levels of potency, which is likely the result of differences in HIV‐1 reporter virus at different chromosomal regions. The related compound chidamide (Figure ), showed better cell tolerance than the commonly used broad‐spectrum HDAC inhibitor suberoylanilide hydroxamic acid (SAHA), and was also able to disrupt viral silencing in primary CD4 + T cells isolated from patients …”
Section: Lras Identified From Small Molecule Screens Exhibit Diverse mentioning
confidence: 99%
“…Chidamide is a low nanomolar HDAC inhibitor of the benzamide class [10], which was approved in 2014 by the China Food and Drug Administration for use in relapsed or refractory peripheral T-cell lymphoma. Chidamide was demonstrated to reactivate latent HIV-1 in cell line models and in primary CD4 T cells from HIV-1-infected individuals [11,12]. Here, we conducted a phase 1b/2a clinical trial to evaluate the safety and efficacy of chidamide to reverse HIV-1 latency in cART-suppressed patients.…”
Section: Introductionmentioning
confidence: 99%